Distribution and Epidemiological Characteristics of Clinical Isolates of A. fumigatus in a Hospital from 2021 to 2023: A Retrospective Study - You Z; Yan Y; Fu T; Yang X; Li Z; Zhou L; Zang F (Infection and Drug Resistance, 2025)
Zhongqiu You,1,* Yunying Yan,2,* Tingting Fu,1 Xiao Yang,1 Zhirui Li,2 Lijun Zhou,2 Feng Zang3 1Department of Infection Management, Chengdu Pidu District People’s Hospital, Chengdu, Sichuan, 611730, People’s Republic of China; 2Department of Disease Control and Prevention, Sichuan Center for Disease Control and Prevention, Chengdu, Sichuan, 610000, People’s Republic of China; 3Department of Infection Management, Jiangsu Provincial People’s Hospital (The First Affiliated Hospital of Nanjing Medical University), Nanjing, Jiangsu, 210029, People’s Republic of China*These authors contributed equally to this workCorrespondence: Feng Zang, Department of Infection Management, Jiangsu Provincial People’s Hospital (The First Affiliated Hospital of Nanjing Medical University), No. 300 Guangzhou Road, Nanjing, Jiangsu Province, 210029, People’s Republic of China, Email 18652921829@163.com Lijun Zhou, Department of Disease Control and Prevention, Sichuan Center for Disease Control and Prevention, No. 6, Zhongxue Road, Wuhou District, Chengdu, Sichuan, 610000, People’s Republic of China, Email zhouliduo1125@163.comObjective: The distribution characteristics of clinical isolates of A. fumigatus were analyzed to provide the basis for the prevention and control of A. fumigatus infection.Methods: From January 2021 to December 2023, the First Affiliated Hospital of Nanjing Medical University collected clinical isolates of A. fumigatus from hospitalized patients for study. Duplicate strains from the same patient in the same area were eliminated, and community-, hospital-, and colonization infections were grouped.Results: A total of 561 clinical isolates of A. fumigatus were identified, with 402 (82.35%) originating from male patients and 159 (17.65%) from female patients. The percentage of individuals aged 51 to 90 years was 78.97% (443/561). With the exception of surgery, which predominantly involved colonization, other departments mainly exhibited community-acquired infections (CAI) (P=0.002). The length of hospital stay was less than < 15– 30 days for most cases in the healthcare-associated infection group (HAI) (P< 0.001). Lower respiratory tract infection accounted for the main site of infection across all three groups (95.37%), with ventilator-associated pneumonia being most prevalent in the HAI group (P< 0.001). The detection rates of A. fumigatus from 2021 to 2023 were 3.89‱, 7.15‱, and 12.50‱, respectively. The detection frequencies of A. fumigatus throughout the three groups exhibited a year-on-year increase (P< 0.001). Sputum samples constituted the main source of clinical isolates for all three groups, accounting for 61 strains (89.71%), 277 strains (78.69%), and 122 strains (86.52%) respectively, followed by bronchoalveolar lavage fluid samples.Conclusion: The detection rate of A. fumigatus has exhibited a consistent upward trend over the past three years, with varying epidemiological characteristics observed across different infection types. It is recommended that medical institutions develop targeted prevention and control measures for A. fumigatus infections based on these unique characteristics.Keywords: community-acquired infections, hospital-acquired infections, A. fumigatus, epidemiology